Strategi Mempertahankan UMKM Bidang Kuliner di Era Digital Marketing pada Masa Pandemi Covid-19 - Dwi Melania; Trisni Handayani (Jurnal EMT KITA, 2023)
The Covid-19 pandemic has had a profound impact on all sectors, one of which is the economy. The impact is very felt for MSME entrepreneurs, not a few MSME entrepreneurs can maintain their business during the pandemic. This study aims to determine the strategies used by SMEs in maintaining their business during the Covid-19 Pandemic. The method used is qualitative with a descriptive approach in data collection techniques by observation, interviews and documentation. In data analysis using conclusion and verification techniques. The initial conclusions put forward are still primary data sources and secondary data. The data that has been obtained will then be analyzed in the form of decomposition and then the results of the data will be analyzed by means of data reduction, data presentation, and conclusions or Reduction Display Conclusions, with target accuracy, socialization, goal achievement and time. The results of this study indicate that 82% of MSMEs in the Cilangkap area of East Jakarta can survive because they have used digital marketing during the pandemic. Further research is suggested that Indonesian MSMEs survive by using digital marketing.